2016
DOI: 10.1093/mnras/stw1726
|View full text |Cite
|
Sign up to set email alerts
|

A stellar-mass black hole population in the globular cluster NGC 6101?

Abstract: Dalessandro et al. observed a similar distribution for blue straggler stars and mainsequence turn-off stars in the Galactic globular cluster NGC 6101, and interpreted this feature as an indication that this cluster is not mass-segregated. Using direct Nbody simulations, we find that a significant amount of mass segregation is expected for a cluster with the mass, radius and age of NGC 6101. Therefore, the absence of mass segregation cannot be explained by the argument that the cluster is not yet dynamically ev… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(104 citation statements)
references
References 72 publications
9
95
0
Order By: Relevance
“…Alternatively, a compact cluster of stellar mass black holes might prevent the cores of these clusters from collapsing (Morscher et al 2013;Lützgendorf, Baumgardt & Kruijssen 2013). Indeed, this possibility has been suggested by Mackey et al (2007) to explain the large core radii of young star clusters in the LMC and more recently by Peuten et al (2016) to explain the absence of mass segregation in NGC 6101. Additional simulations will be necessary to distinguish between these possibilities.…”
Section: The N -Body Modelsmentioning
confidence: 96%
“…Alternatively, a compact cluster of stellar mass black holes might prevent the cores of these clusters from collapsing (Morscher et al 2013;Lützgendorf, Baumgardt & Kruijssen 2013). Indeed, this possibility has been suggested by Mackey et al (2007) to explain the large core radii of young star clusters in the LMC and more recently by Peuten et al (2016) to explain the absence of mass segregation in NGC 6101. Additional simulations will be necessary to distinguish between these possibilities.…”
Section: The N -Body Modelsmentioning
confidence: 96%
“…In other cases, there are other physical explanations that cannot be ruled out and are more plausible. Radially-biased anisotropy in the velocity distribution or the presence of dark remnants such as white dwarfs, neutron stars (Illingworth & King 1977;den Brok et al 2014) and BHs (Lützgendorf, Baumgardt & Kruijssen 2013;Peuten et al 2016;Baumgardt et al 2019) can mimic the dynamical signatures previously ascribed to an IMBH, in particular the increase in the central velocity dispersion. The same goes for high-velocity stars found in the cores of some GCs (Meylan, Dubath & Mayor 1991;Gunn & Griffin 1979;Lützgendorf et al 2012), which may suggest interaction with an IMBH but can in fact simply result from interactions with a binary system (Lützgendorf et al 2012) or represent 'potential escapers', stars above the local escape velocity that are energetically unbound but trapped inside the Jacobi surface for several orbits before escaping the cluster (Fukushige & Heggie 2000;Claydon, Gieles & Zocchi 2017;Daniel, Heggie & Varri 2017).…”
Section: Introductionmentioning
confidence: 93%
“…Such studies are extremely computationally intensive for systems as massive as UCDs. On the other hand, Peuten et al (2016) and Baumgardt & Sollima (2017), constrain the retention fraction of dark remnants in lower mass GCs, which allows us to deduce implications for UCDs.…”
Section: Calculating M/l V Ratiosmentioning
confidence: 99%
“…This is a conservative assumption as Baumgardt & Sollima (2017) and Peuten et al (2016) constrain the retention fraction to be less than about 50 per cent for globular clusters (GCs) based on a detailed study of their observed mass segregation. With this normalisation condition, and assuming two possible radius-mass relations for GCs and for UCDs, we can estimate the likely values of the retention fraction of stellar remnants (neutron stars and black holes) as a function of birth system mass, M. One possibility for the R(M) relation is to assume the observed radii of clusters (typically about 3 pc) and of UCDs (Eq.…”
Section: Retention Fraction Of Dark Remnantsmentioning
confidence: 99%